Development of an Improved in vitro Model of Bovine Trophectoderm Differentiation - Ortega, M. Sofia; Rizo, Jason A.; Drum, Jessica N.; O'Neil, Eleanore V.; Pohler, Ky G.; Kerns, Karl; Schmelze, Amanda; Green, Jonathan; Spencer, Thomas E. (Frontiers in Animal Science, 2022)
The mechanisms regulating early stages of placentation and trophectoderm differentiation in the ruminant conceptus remain poorly understood. Here we present a model of trophectoderm (TE) differentiation in vitro from outgrowths of individual in vitro derived embryos. Cell outgrowths expressed markers of mononucleate (MNC) and binucleate (BNC) TE cells. The percentage of BNC ranged from 14 to 39% in individual outgrowths as determined by flow cytometry. Pregnancy-associated glycoproteins (PAGs), produced by BNC, were measured in culture media on days 35 to 54. Continuous secretion of PAGs was observed and indicative of BNC functionality. Gene expression was evaluated in 20 embryo cell outgrowths derived from two different sires. Expression of HAND1, which is involved in TE differentiation, and CSH2, a BNC-specific gene, was altered in cell outgrowths between the two sires tested. Single-cell RNA-seq analysis of day 40 TE cell outgrowths revealed 11 distinct cell populations, with specific clusters genes involved in TE lineage specification, proliferation, and differentiation. In addition, whole -RNAseq analysis was performed in day 35 and 40 TE cell outgrowths and confirmed sustained expression of genes expressed by BNC, such as CSH2 and some PAGs. The developed in vitro bovine embryo outgrowth culture found evidence for MNC and BNC differentiation and continuous production of PAGs, recapitulating key features of early bovine placenta development. This model can be used to understand the developmental biology of TE cells, provide insights into paternal influences on TE differentiation, and impact our understanding of early pregnancy loss in cattle.